2022
DOI: 10.1002/pbc.29600
|View full text |Cite
|
Sign up to set email alerts
|

Second cancer risk in childhood cancer survivors treated with intensity‐modulated radiation therapy: An updated analysis of more than 10 years of follow‐up

Abstract: Background: It is unclear how intensity-modulated radiation therapy (IMRT) impacts long-term risk of second malignant neoplasms (SMNs) in childhood cancer patients. Procedure: Patients aged ≤21 years treated with IMRT between 1998 and 2009 and who survived ≥5 years after IMRT were included. SMN site in relation to isodose level (IDL) of IMRT was evaluated. Standardized incidence ratios (SIR) and excess absolute risks (EAR) were calculated. Cumulative incidences were estimated with death as a competing risk.Res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Of note, a recent study reported a 10-year cumulative incidence of solid SPC of 1.8% after intensity modulated radiotherapy for pediatric cancer [4] , in line with estimates from conventional radiotherapy despite a larger low-dose volume. Therefore, more clinical evidence is required to understand the effect of low-doses on SPC risks [18] , when available clinical data are so far not indicating an increased risk.…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…Of note, a recent study reported a 10-year cumulative incidence of solid SPC of 1.8% after intensity modulated radiotherapy for pediatric cancer [4] , in line with estimates from conventional radiotherapy despite a larger low-dose volume. Therefore, more clinical evidence is required to understand the effect of low-doses on SPC risks [18] , when available clinical data are so far not indicating an increased risk.…”
Section: Discussionsupporting
confidence: 66%
“…However, the low-dose bath is higher with PAT compared to intensity modulated proton therapy (IMPT) [2] . Therefore, and in particular for pediatric patients, concerns exist with regards to radiation-induced second primary cancers (SPC) with PAT, as the impact of low doses on SPC risks is still unclear [3] , [4] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, long-term (11 years) follow-up data from a single center with 325 patients treated with intensity-modulated photon RT revealed that solid secondary malignancy developed in 11 patients and the 10- and 15-year cumulative incidence of secondary malignancy were 1.8% and 3.5%, respectively. Eight among 11 solid secondary malignancies developed within the intensity-modulated photon RT field, 1 within the intermediate-dose area, and only 1 was out-of-field [ 51 ]. Solid secondary malignancies included high-grade glioma (n= 3), osteosarcoma (n=3), colon cancer (n=2), thyroid cancer (n= 1), presumed sarcoma (n=1), and unknown primary (n=1).…”
Section: Late Effects Following Rt For Opgmentioning
confidence: 99%
“…Also, Indelicato et al [ 53 ] reported a 10-year cumulative incidence of 3.1% in 1,713 children treated with PBT and 1.7% in 1,676 children without germline mutation. They observed that all 5 high-grade gliomas (in children without genetic syndrome) developed in the high-dose region same as the intensity-modulated photon RT series [ 51 ]. A retrospective cohort study of 558 adult patients treated with PBT showed slightly reduced incidence of secondary neoplasm compared to matched cohort from the Surveillance, Epidemiology, and End Results cancer registry treated with X-rays (5.2% vs. 7.5%) [ 54 ].…”
Section: Late Effects Following Rt For Opgmentioning
confidence: 99%